Laparoscopic management of a complicated case of Wilkie's syndrome: A case report. (2017) - Khodear, Yehya; Al-Ramli, Wisam; Bodnar, Zsolt
Highlights: Surgical intervention is the mainstay in complicated cases of SMA syndrome and in refractory cases to conservative management. Successful management of a complicated case of Wilkie's Syndrome via duodenojeujenostomy is feasible using a laparoscopic approach. Advantages of laparoscopic approach over open surgery include rapid recovery time, reduced post-operative pain and shorter hospital stay. Abstract: Introduction: Superior mesenteric artery (SMA) syndrome also known as Wilkie's syndrome is a rare condition caused by the entrapment of the third part of the duodenum between the aorta and the SMA. The incidence of Wilkie's syndrome range between 0.013% and 0.3%. The normal angle between the aorta and SMA has been described to range between 38° and 65°, whereas in Wilkie's syndrome this angle is reduced to less than 20° causing gastric outlet obstruction. Case presentation: We report a case of a previously diagnosed 43 year-old male with SMA syndrome, whom had been conservatively managed for 5-years for recurrent admissions with symptoms of gastric outlet obstruction. During his last admission, CT abdomen demonstrated gastric pneumatosis and portal venous gas requiring urgent surgical intervention. Duodenojejunostomy was successfully performed using laparoscopic technique. Discussion: SMA syndrome is thought to occur secondary to the rapid and excessive weight loss leading to the reduction of the mesenteric fat around the aorta and SMA, thereby reducing the normal angle between the two arteries. Conservative medical management is usually the first line of treatment in uncomplicated cases. Surgical management is usually reserved only after failed conservative management or complicated cases, at which time either an open or laparoscopic surgical approach is undertaking. Conclusion: Surgical intervention is the mainstay in complicated cases of SMA syndrome and in refractory cases to conservative management. Advantages of laparoscopic approach over open surgery include rapid recovery time, reduced post-operative pain and shorter hospital stay.